EFEITOS DO HALOTANO ASSOCIADO A HIPERCAPNIA SOBRE A HEMODINAMICA RENAL - Yong, L. C.; Vianna, P. T.G.; Braz, J. R.C.; Vane, L. A. (My University, 1979)
In eighteen dogs, the effects of halothane (0.75% and 1.5%) associated with a norm and hypercapnia (PaCO2 from 30 to 80 mmHg) on renal hemodynamics were studied. Determinations of mean arterial pressure, venous pressure, heart rate and renal arterial resistence were made. Based on the results, they have concluded that halothane disturbs the important functions of kidney (decreases effective renal plasmatic flow, glomerular filtration rate, filtration percentage, urinary flow, urinary excretion of sodium and potassium) and increases renal arterial resistence.
Effects of halothane associated with hypercapnia on renal hemodynamics